DECREASE OF BREAKAGE OF HIGH-STRENGTH WIRE AT TWIST OF METAL CORD FROM IT ON CARS OF DOUBLE TORSION - V. A. Birukov; Ju. V. Fektistov; A. V. Vedeneev (Литьë и металлургия)
Influence of technological parameters of deformation on solidity losses at the example of super-strength wire with diameter 0,20 mm is considered. Difference of influence of separate types of deformation from influence of summation influence on solidity losses is shown.